Property Management Software (PMS) Application Effect Toward Property Management Operation in Johor Bahru - Azreen Azman,; Mohd Hafizal Ishak, (Research in Management of Technology and Business, 2024)
Recent technological advances have notably changed property management. Johor Bahru's vibrant real estate scene offers an excellent backdrop to explore how Property Management Software (PMS) applications impact operational efficiency and efficacy. However, the specific landscape of PMS usage in Johor Bahru is largely unexplored, lacking essential information about software availability. This knowledge gap poses risks, as the absence of a clear understanding of PMS benefits, drawbacks, and best practices exposes companies to potential inefficiencies, decreased tenant satisfaction, and financial losses. The study aims to examine current property management software practice and to investigate the property management software application effect toward property management operation in Johor Bahru. The qualitative method was used through semi-structured interview with property management professionals and analysing the data using content analysis. The result shows that the current property management software align with PropTech 4.0, yet lacks full integration of emerging tech such as blockchain and 3D scanning. However, it notably boosts operational efficiency, reduce costs, and enhances tenant experience, fostering better integration and collaboration. This emphasizes the need for adapting property management software to emerging technologies, offering valuable insights for Johor Bahru professionals and stakeholders.